A Systematic Review of Physical Rehabilitation of Facial Palsy - Vaughan, Annabelle; Gardner, Danielle; Miles, Anna; Copley, Anna; Wenke, Rachel; Coulson, Susan (Frontiers in Neurology, 2020)
Central facial palsy (CFP) is a frequent and debilitating sequela of stroke and brain injury, causing both functional and aesthetic deficits as well as a significant adverse effect on quality of life and wellbeing. Current literature reports many cases of acquired CFP that do not recover spontaneously, and more information is needed regarding the efficacy of current physical therapies used in this population. A systematic search of eight electronic databases was performed from database inception to December 2018. Grey literature searches were then performed to identify additional articles. Studies were included if they addressed physical rehabilitation interventions for adults with acquired CFP. Reasons for exclusion were documented. Independent data extraction, quality assessment, and risk of bias assessment followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Following abstract screening, a total of 13 full-text articles were identified for independent screening by two reviewers. This included four randomized control trials, two non-randomized control trials, one cohort study, and six prospective case series studies. Twelve out of the 13 included studies reported on facial palsy as a sequela of stroke; one study reported facial palsy secondary to brain injury. A total of 539 participants received intervention for facial palsy across the 13 included studies. Therapy design, length and frequency of intervention varied across the studies, and a wide range of outcome measures for muscle strength and facial movement were used. Improvement in facial muscle strength and/or movement was reported across all 13 studies, and positive changes in other outcome measures such as swallow function and quality of life were also shown. The quality of the evidence was low overall, and most studies were found to have high risk of bias. All the studies in this review report improvement of facial movement and/or function and indicate potential benefit of physical rehabilitation for CFP. Methodological limitations and heterogeneity of design affect the strength of the evidence and prevent reliable comparison between intervention methods. The findings provide some support for physical rehabilitation of central facial palsy and highlight the need for further well-designed rigorous research to better guide clinical planning.